2019
DOI: 10.3813/aaa.919395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Airborne Ultrasound Exposure on Behavioural and Electrophysiological Measures of Auditory Function

Abstract: Regulations on safe ultrasound exposure limits are based on a very limited number of studies, which have only considered audiometric threshold shifts as indicators of hearing deficits. The purpose of the current study was to assess the effects of exposure to high-intensity ultrasound on a range of measures of hearing function, which included audiometric thresholds, as well as subclinical measures of hearing deficits: speech-in-noise understanding, supra-threshold auditory brainstem response wave I amplitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Log wave amplitude was used as the dependent variable ( Bramhall, Konrad-Martin, McMillan, Griest, 2017 , Bramhall, McMillan, Gallun, Konrad-Martin, 2019 , Carcagno, Di Battista, Plack, 2019 ). Wave I and wave V amplitudes were modeled jointly.…”
Section: Methodsmentioning
confidence: 99%
“…Log wave amplitude was used as the dependent variable ( Bramhall, Konrad-Martin, McMillan, Griest, 2017 , Bramhall, McMillan, Gallun, Konrad-Martin, 2019 , Carcagno, Di Battista, Plack, 2019 ). Wave I and wave V amplitudes were modeled jointly.…”
Section: Methodsmentioning
confidence: 99%
“…A further study into the effects of 40 kHz ultrasound on human hearing [134] found no evidence of a threshold shift indicative of potential hearing loss. They also found no evidence of brain activity (through EEG) in response to the ultrasound frequency or its lower harmonics.…”
Section: G Safetymentioning
confidence: 93%
“…Unlike audible sound, extreme levels of ultrasound would not cause noticeable discomfort that warns the user that their hearing is at risk. The highest pressure in the sound field is within the focal point(s), which may be in excess of 140 dB [130], [131], [134]. This pressure is highly localized, attenuating away from the focal point(s).…”
Section: G Safetymentioning
confidence: 99%
“…Ultraleap (Bristol, UK) is a company that commercializes ultrasonic phased arrays for haptic applications related to automotive [31], digital signage [32], and AR/VR [33] applications. The company has also been exploring the effects on humans of high intensity ultrasound exposure [34] and has been releasing multiple prototypes that explore optimized array designs [35,36]. For example, transducer array in a Fibonacci spiral arrangement can suppress unwanted secondary focal points [37].…”
Section: Related Workmentioning
confidence: 99%